Traumatic Testicular Dislocation Associated with Lateral Compression Pelvic Ring Injury and T-Shaped Acetabulum Fracture - Daniel Howard Wiznia; Mike Wang; Chang Yeon-Kim; Paul Tomaszewski; Michael P. Leslie (Case Reports in Orthopedics)
We report a case of a unilateral testicular dislocation to the superficial inguinal region associated with a lateral compression type pelvic ring injury (OTA classification 61-C3.3a2, b2, c3) and left T-shaped acetabulum fracture (OTA classification 62-B2) in a 44-year-old male who was in a motorcycle accident. The testicular dislocation was noted during the emergency department primary survey, and its location and viability were verified with ultrasound. The testicle was isolated during surgical stabilization of the left acetabulum through a Pfannenstiel incision and modified-Stoppa approach and returned through the inguinal canal to the scrotum. In follow-up, the patient did not suffer urologic or sexual dysfunction. All motorcycle collision patients presenting with pelvic ring injuries or acetabulum fractures should be worked up for possible testicular dislocation with a scrotal exam. Advanced imaging and a urologic consult may be necessary to detect and treat these injuries.